Adverse reactions and alleged allergy to local anesthetics: Analysis of 331 patients. Issue 7 (19th May 2013) - Batinac, Tanja; Sotošek Tokmadžić, Vlatka; Peharda, Vesna; Brajac, Ines
Abstract The aim of this study was to determine the prevalence of true local anesthetic (LA) allergy among patients referred for suspected hypersensitivity and to describe the main characteristics of adverse drug reactions (ADR) induced by LA in our population. We retrospectively analyzed the medical files of patients referred to the Department of Dermatovenereology, University Hospital Center Rijeka, Rijeka, Croatia, for the investigation of LA hypersensitivity in the period between January 2000 and December 2012. A total of 331 patients underwent skin testing and, in cases of negative results, subcutaneous exposition to LA. In patients with suspected delayed reaction, patch test was performed. Altogether, 331 patients reported 419 independent ADR occurring during 346 procedures. Most commonly, patients reported having only one ADR, but 41 (12.4%) of them had two reactions, 14 (4.2%) had three, five (1.5%) had four and in one patient (0.3%) five ADR to LA were observed. The majority of reactions occurred during dental procedures when most commonly lidocaine and articaine were used. Local reactions were reported in 44 patients, whereas 490 general symptoms occurred during 375 independent ADR in 287 patients. The most common symptoms were cardiovascular system reactions in 89 patients (18.2%). Allergic reaction was detected in three patients (0.91%). One patient showed immediate‐type reaction to bupivacaine and two patients had a delayed‐type reaction to lidocaine. Adverse reactions to LA are common and are mostly due to their pharmacological properties and drug combinations or psychogenic origin. Allergic accidents to LA are rare.